GERMANIY ATOMLARÍNÍŃ ELEKTRONLAR MENEN NURLANDÍRÍLǴAN KREMNIY-GERMANIYDE DIVAKANSIYALARDÍŃ PAYDA BOLÍWÍNA TÁSIRI - Akimova, J.; Otarbaev, A.; Yuldashov, D. (SCIENCE and SOCIETY, 2023)
In this article, the shift of the spectrum towards low frequencies indicates a decrease in the energy of infrared absorption, and as a result, does not change it the concentration of divacanations.